2014
DOI: 10.5324/nje.v24i1-2.1823
|View full text |Cite
|
Sign up to set email alerts
|

Multiple births and maternal mental health from pregnancy to 5 years after birth: A longitudinal population-based cohort study

Abstract: Background: There is a lack of population-based studies on multiple births and maternal mental health. Having a high-risk pregnancy by bearing two or more children is a stressful life event, and the challenges of parenting two or more children probably also lead to a high level of parental stress. There are a few results on multiple births and maternal mental health from studies on in vitro fertilization samples. The only previous cohort study on multiple birth and maternal mental health included a single meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For example, in the Term Breech Trial, 10.1% of women in the planned CS group and 10.8% of women in the planned VB group scored >12 on the EPDS at 3 months post partum . The increase in elevated depression scores observed here might be attributed to the fact that almost 50% of births in our sample occurred preterm, and depression has been found to be more prevalent among mothers of preterm infants, or that a moderate proportion of women in both groups used assisted conception methods, which has also been associated with increased emotional stress . However, it is possible that giving birth to and caring for twins independently predisposes women to postpartum depression, and this finding deserves further investigation.…”
Section: Discussionmentioning
confidence: 56%
“…For example, in the Term Breech Trial, 10.1% of women in the planned CS group and 10.8% of women in the planned VB group scored >12 on the EPDS at 3 months post partum . The increase in elevated depression scores observed here might be attributed to the fact that almost 50% of births in our sample occurred preterm, and depression has been found to be more prevalent among mothers of preterm infants, or that a moderate proportion of women in both groups used assisted conception methods, which has also been associated with increased emotional stress . However, it is possible that giving birth to and caring for twins independently predisposes women to postpartum depression, and this finding deserves further investigation.…”
Section: Discussionmentioning
confidence: 56%
“…Mothers’ depression has repeatedly been shown to be associated with sleep problems in their offspring (Martin, Hiscock, Hardy, Davey, & Wake, 2007; Zuckerman, Stevenson, & Bailey, 1987). From pregnancy and throughout the preschool years, the peak level of maternal depressive symptoms is when the child is between 1.5 and 3 years of age (Ystrom et al, 2014). Maternal depression is related to parental behavior, and research has suggested that maternal depression may affect child development on several domains, including cognitive and language development (Grace, Evindar, & Stewart, 2003; Sohr-Preston & Scaramella, 2006); mental health problems (Goodman et al, 2011; Lieb, Isensee, Höfler, Pfister, & Wittchen, 2002); suboptimal diet (Ystrom, 2012; Ystrom, Barker, & Vollrath, 2012); and a number of different social, emotional, and behavior problems (Goodman et al, 2011; Grace et al, 2003; Nilsen, Gustavson, Røysamb, Kjeldsen, & Karevold, 2013).…”
mentioning
confidence: 99%
“…An epigenetic control of growth‐factor genes in the twin‐fetuses might have such effects. One should also keep in mind that mothers of twins are more likely to be affected by psychological distress (Ystrom et al, ), and that families with twins may perhaps be more likely to experience economic strain. Such psychosocial and economic factors might influence the postnatal weight gain of the children.…”
Section: Discussionmentioning
confidence: 99%